The Chignecto Ship Railway [electronic resource] : the substitute for the Baie Verte canal. - Ketchum, H. G. C. (Henry George Clopper), 1839-1896 ([Fredericton, N.B.? : s.n., 1892)
Caption title. Attributed to H.G.C. Ketchum --Canadiana 1867-1900. Electronic reproduction. Mode of access: Internet. 44